Potential Anti-Depressive Effects and Mechanisms of Zhi-Zi Hou-Po Decoction Using Behavioral Despair Tests Combined With in Vitro Approaches - Bai, Yongtao; Dai, Guoliang; Song, Lihua; Gu, Xiaolei; Ba, Ning; Ju, Wenzheng; Zhang, Wenzhou (Frontiers in Pharmacology, 2022)
Zhi-Zi Hou-Po Decoction (ZHD) has been widely used in the treatment of depression for centuries. This study aimed to investigate the antidepressant effects of the water extract of ZHD (ZHD-WE) and ethanol extract of ZHD (ZHD-EE) using behavioral despair tests in mice, and to further explore the neuroprotective effects in a PC12 cell injury model induced by corticosterone (CORT). Mice were divided into the a control group, ZHD-WE groups, ZHD-EE groups and the fluoxetine group. The forced swimming test (FST) and tail suspension test (TST) were used to screen the antidepressant effects of ZHD-WE and ZHD-EE after oral administration for seven consecutive days. The level of brain-derived neurotrophic factor (BDNF) in the hippocampus was determined by ELISA. The MTT, lactate dehydrogenase (LDH) and flow cytometry analysis were performed to elucidate the neuroprotective effect of ZHD-EE on a PC12 cell injury model. Additionally, the mRNA and proteins expression of apoptotic molecules Bax, Bcl-2 and BDNF mRNA and proteins were detected by RT-PCR and western blot assay. In vivo, ZHD-EE at concentrations of 8 g·kg-1 and 16 g·kg-1 significantly decreased the immobility time in the TST and FST, and increased the BDNF levels in the hippocampus. While ZHD-WE at concentrations of 4 g·kg-1, 8 g·kg-1, and 16 g·kg-1 had no significant effect on the immobility time in the TST, and only the 16 g·kg-1 dose group significantly decreased the immobility time in the FST. In vitro, the obtained results showed that PC12 cells pre-incubated with ZHD-EE at concentrations of 100 and 400 μg·mL-1 improved cell viability, decreased LDH release, and reduced the apoptosis rate of PC12 cells. Moreover, ZHD-EE significantly increased the mRNA and proteins expression of Bcl-2 and BDNF mRNA and proteins, and decreased Bax mRNA and protein expression. ZHD-EE significantly improved despair-like behavior in mice, and its mechanism may be related to BDNF upregulation in the hippocampus. Further study showed that ZHD-EE had a protective effect on corticosteroneCORT-induced injury in PC12 cells by upregulating the expression of the BDNF and restoring the Bcl-2/Bax balance.